Furaṣ al-Tafāʿul ʿinda Taʿallum al-Lughah al-Thāniyah fī Qāʿat al-Dars - Himmatul Mahmudah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
There is a common belief that learning a second language involves learning rules, especially learning the correct vocabulary and pronunciation. The development of these laws in all contexts is a natural extension of grammar. Assume that the use of language is not different in the position of the first language than in the positions of multiple languages. All those required to speak a second language successfully has to activate correct formulas, which is to say the same thing as well as what native speakers said in his/her language. We often find such conditions while in the process of language learning in the classroom, which is the main driving force in learning the second language the learners are exposed to. Furthermore, one of the key to success in learning a second language is the ability to absorb (assimilation). The form of language learning process in the classroom is the concept which allows the native speakers to assess and understand the pronunciation of non-native speakers and vice versa. This program provides opportunities for interaction in the classroom and attention of all learners to the events of language learning which makes the process of second language acquisition runs successfully, especially for the learners of non-native speakers.